Design of Scraper Conveyor for Palm Oil Mills Industry - Ng, Tzer Xuan; Sia, Chee Kiong (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The handling process of oil palm fresh fruit bunch (FFB) from its loading site to the sterilizer in a palm oil mill is a crucial process, and should be carryout efficiently conceivably to maintain the quality of crude palm oil (CPO) extracted. There are a small number of machines being used in palm oil industry are incapable to transport the desired amount of palm oil fruit bunches, which practically influencing the CPO extraction progress. To overcame that, a scraper conveyor for the use of oil palm FFB transportation from reception site to sterilizer in palm oil mill is designed, to replace handling mechanism of human operated machine. A simulated computer aided design (CAD) model for the conveyor designed had been developed, by referring to suitable resources of mechanical parts supplier. The designed conveyor had a theoretical transportation capacity of 150 tonnes per hour, it can handle FFB to 10m higher from the inlet level. The length of the conveyor designed can be altered accordingly to suit specific situation since it is composed from various number of casing that detachable.